Implementation of Community Empowerment through Creative Industry: Pandan Weaving MSME in Grenggeng Village, Karanganyar - Amanah, Rizqi Ridlo; Widodo, Naufal Rafi; Ngatikoh, Siti; Mangole, Annisa (Proceedings Series on Social Sciences & Humanities, 2025)
This research explores empowerment strategies for Micro, Small, and Medium Enterprises (MSMEs) in the tourism sector through the adoption of digital innovation in Grenggeng Village, Karanganyar District, Kebumen. The village optimizes the potential of local resources, particularly pandan weaving products, as the main commodity of the creative industry. MSME empowerment is realized through the formation of the Productive Business Group Margo Rahayu and collaboration with the Village-Owned Enterprise, which plays a role in supporting the production and marketing of local products. Through a participatory approach, the community is actively involved in economic activities, strengthening managerial capabilities, market access, and using digital technology. The research results indicate that although there are obstacles, such as limited raw material supply and climate change, collaboration between the community, village government, and related agencies can improve community welfare and preserve local culture. This study suggests enhancing human resource capacity and technological support to strengthen the competitiveness of digitally-based MSMEs in tourism villages.